ChemInform Abstract: Direct Arylation of Pyridines Without the Use of a Transition Metal Catalyst. Issue 48 (2nd December 2014) - Li, Yahui; Liu, Wei; Kuang, Chunxiang
Abstract The direct arylation of electron‐deficient heterocycles, such as (I), (V), (VIII), and (X) with arylhydrazine hydrochlorides (II) without any catalyst and co‐oxidant is described.